2008
DOI: 10.1007/s00710-007-0222-4
|View full text |Cite
|
Sign up to set email alerts
|

Pre-metamorphic melt infiltration in metasediments: geochemical, isotopic (Sr, Nd, and Pb), and field evidence from Serie dei Laghi (Southern Alps, Italy)

Abstract: SummaryGradual transitions from K-feldspar free gneisses to K-feldspar bearing augengneisses are sometimes observed in metamorphic terranes. They have been explained with metasomatic porphyroblastic growth connected with regional metamorphism, or with pre-metamorphic presence of magmatic megacrysts. A transition of this kind can be observed in the Serie dei Laghi (Southern Alps, Italy), where coarse-grained metaarenites (Cenerigneiss) grade into Ceneri augengneisses with large K-feldspar porphyroclasts, and ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…In any case, the vestiges of Permo-Triassic volcanic events aligned along a 300-km E-W belt in the South Alpine region indicate the existence of tectonic structures that were effective at least since the Variscan tectonomagmatic phase, well before the Alpine cycle. Beccaluva et al, 2007), the Tertiary calc-alkaline mafic rocks from Adamello (Alagna et al, 2010;Kagami et al, 1991), Triassic shoshonite rocks from the dolomites (Bonadiman et al, 1994), Permian high-K calc-alkaline basalts and gabbros (Macera et al, 1994;Rottura et al, 1998), and Permian andesites from Lugano and Val di Sesia (Sinigoi et al, 2016); since Nd isotopic values are not available for the metamorphic rocks of the studied area, isotopic values of the basement are referred to a neighboring sector of the South Alpine region characterized by similar micashists and paragneisses (Pinarelli et al, 2008).…”
Section: Tectonics 4 Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In any case, the vestiges of Permo-Triassic volcanic events aligned along a 300-km E-W belt in the South Alpine region indicate the existence of tectonic structures that were effective at least since the Variscan tectonomagmatic phase, well before the Alpine cycle. Beccaluva et al, 2007), the Tertiary calc-alkaline mafic rocks from Adamello (Alagna et al, 2010;Kagami et al, 1991), Triassic shoshonite rocks from the dolomites (Bonadiman et al, 1994), Permian high-K calc-alkaline basalts and gabbros (Macera et al, 1994;Rottura et al, 1998), and Permian andesites from Lugano and Val di Sesia (Sinigoi et al, 2016); since Nd isotopic values are not available for the metamorphic rocks of the studied area, isotopic values of the basement are referred to a neighboring sector of the South Alpine region characterized by similar micashists and paragneisses (Pinarelli et al, 2008).…”
Section: Tectonics 4 Discussionmentioning
confidence: 99%
“…Permo-Triassic basic magmas characterized by calc-alkaline/shoshonite affinity are widespread in the South Alpine domain (Figure 8), suggesting that the underlying mantle has been metasomatized by subductionrelated fluids. Some authors (e.g., Dallagiovanna et al, 2009;Giacomini et al, 2006;Spiess et al, 2010;Stampfli & Borel, 2002;von Raumer et al, 2003) relate the Permian-Triassic orogenic volcanism observed in the southern Variscides to Carboniferous subduction events leading to northward consumption of the (Nimis et al, 2012, and references therein) and that of the South Alpine basement (Pinarelli et al, 2008) are reported for comparison.…”
Section: Conclusive Remarksmentioning
confidence: 99%
See 2 more Smart Citations
“…Augen gneisses were also interpreted as results of metasomatic processes in metasediments. For instance, Pinarelli et al (2008) explained development of K-feldspar bearing augen gneisses by a model of infiltration of residual hydrous magmas into a metasedimentary protolith. Other types of augen gneisses are thought to be formed by segregation of feldspar (and quartz) crystals and aggregates during migmatization (Mehnert 1968).…”
Section: Introductionmentioning
confidence: 99%